Analyzing development patterns in research networks and technology - Patrick Wolf; Tobias Buchmann (Review of Evolutionary Political Economy, 2021)
The present paper analyzes development patterns in research networks and technology as well as their co-evolution by the example of the currently highly transformative German automotive industry. We therefore introduce a consistent network-based approach for measuring change in research networks and the technological composition of patents. Our results show that the applied method is particularly useful for identifying structural similarities and main structural changes in research and patent networks. Further, the investigation of the co-evolutionary processes indicates that, regarding the German automotive industry, changes in technology lead to structural changes in the research network.
Keywords: O3; O30; 320; Technological change; Innovation networks; Network dynamics; Co-evolution